Physical activity and health promotion for nursing staff in elderly care: a study protocol for a randomised controlled trial. Issue 10 (6th October 2020) - Otto, Ann-Kathrin; Pietschmann, Juliane; Appelles, Luisa-Marie; Bebenek, Michael; Bischoff, Laura L; Hildebrand, Claudia; Johnen, Bettina; Jöllenbeck, Thomas; Kemmler, Wolfgang; Klotzbier, Thomas; Korbus, Heide; Rudisch, Julian; et al.
Abstract : Introduction: Nursing staff is burdened by high workload and stress. Furthermore, heavy lifting, as well as transferring nursing home residents, cause lumbar tissue damage and back pain. Exercise intervention studies to reduce work-related problems are rare and the evidence for efficacy of studies among nurses is limited. Studies including targeted analysis of requirements are necessary to generate effective recommendations and tailored interventions for health promotion programmes. The purpose of this multicentred intervention study is to identify work-related problems, to implement health promotion programmes and to evaluate their effectiveness. Methods and analysis: A randomised controlled trial will be conducted, including a total of 48 nursing home facilities in eight regions of Germany with an estimated sample size of 700 nurses. Standardised ergonomics and posture training (10 weeks, once a week for 20–30 min) and subsequently, back-fitness training (12 weeks, once a week for 45–60 min) will be administered. Following the implementation of standardised health promotion programmes, further demand-oriented interventions can be implemented. The perceived exposure to work-related demands, work-related pain in different parts of the body, health-related quality of life, perceived stress, work-related patterns of behaviour and experience, presentism behaviour, work environment as well as general needs and barriers to health promotion, will be assessed at baseline (pre-test), at 10 weeks (post-test, after ergonomics training), at 22 weeks (post-test, after back-fitness training) and at 34 weeks of the programme (follow-up). Ethics and dissemination: The study was reviewed and approved by the local ethics committee of the University of Hamburg (AZ: 2018_168). The results of the study will be published in open-access and international journals. Furthermore, the results will be presented in the participating nursing homes and at national and international conferences. Trial registration number: DRKS.de (DRKS00015241).